Study of design criteria for the Ayung River estuary area as an urban riverfront park in Denpasar City, Bali - I Made Agus Dharmadiatmika; Kadek Edi Saputra; Naniek Kohdrata; Hinako Yamagami (Universitas Mercu Buana, 2023)
Public green open space management currently tends to be in strategic areas in Denpasar City, such as the Sanur coastal area, city center, and city roads. This centralization will, in time, create a feeling of saturation and require a new atmosphere and unequal development. One of the efforts is to explore the potential of vacant land in coastal areas that have yet to be touched by development, one of which is the estuary of the Ayung River. The community currently uses the edge of the estuary of the Ayung River for recreational activities. The first step is to have a design that supports this function, especially since this area has ecological benefits for the city. The research objectives can accommodate the community's needs, managers, regional potential, and sustainable landscape design approaches. The analysis technique used is descriptive analysis technique using walkability analysis and triangulation approaches. The results of the study integrate the theory of sustainable coastal area landscape design by producing design criteria, namely: Socio-cultural function design criteria with the principle approach of environmental community involvement, Economic function design criteria with the application of the economic tenets involving Small and Medium Enterprises (SMEs), Environmental function criteria with the principles of waste management, linkage criteria with an energy efficiency function approach, and aesthetic function design criteria with a safe and comfortable material principle approach.